Conducting the National Health and Morbidity Survey 2023 in Malaysia with focus on methodology and main findings on non-communicable diseases - Halizah Mat Rifin; Muhammad Fadhli Mohd Yusoff; Hamizatul Akmal Abd Hamid (Scientific Reports)
Abstract The National Health and Morbidity Survey (NHMS), which focuses on non-communicable diseases (NCDs), their risk factors and healthcare demand, is a cross-sectional, nationwide, population-based survey conducted every four-year cycle since 2011. NHMS 2023 was the 7th cycle of NCDs, their risk factors and healthcare demand, which aimed to monitor trends in diseases and healthcare utilisation. This article outlines the methodology, sociodemographic characteristics, and overall findings from the population surveyed in 2023 regarding NCDs, their risk factors, and various health-related topics. This survey utilised a two-stage stratified random sampling design and encompassed fifteen main scopes, with sample sizes calculated to meet the specific requirements of each scope. Conducted from July to September 2023, it involved the random selection of 499 enumeration blocks(EBs) by the Department of Statistics Malaysia (DOSM) across all states and federal territories in Malaysia. The step resulted in the selection of 5,988 living quarters (LQs). Data collection methods included validated questionnaires administered through face-to-face interviews and self-administered questionnaires, alongside clinical assessments and blood investigations using calibrated devices. To ensure the high quality of the collected data, we implemented stringent quality control measures. Furthermore, we applied complex sampling analyses to ensure that the findings accurately represented the population in Malaysia. The survey received responses from 13,616 individuals out of the 5,006 LQs that were successfully visited, resulting in an overall response rate of the survey of 83.2%, which includes individuals aged 5 years and above. A substantial segment of the population lived in urban regions, comprising 77.6% of the total. About half of the population consisted of males (51.9%), Malay (54.6%), and individuals who had attained secondary education (54.2%). Additionally, 20.0% of the population were within the age range of 30 to 39 years. The weighted prevalence of diabetes was 15.6%, hypertension 29.2%, hypercholesterolaemia 33.3%, overweight and obesity 54.4%. Depression among adults was 4.6%, while mental health problems among children were reported at 16.5%. The current tobacco smokers prevalence was 19.0%, and 29.9% of adults in Malaysia were physically inactive. The known asthma prevalence among adults was 6.2%, while the current asthma among children was 3.4%. Additionally, 37.7% of adults experienced sleep insufficiency. The results indicate that the higher proportion of diabetes, hypertension, and hypercholesterolaemia, particularly among the young age group, and the high prevalence of overweight and obesity, as well as mental health problems,  are making the healthcare system deal with more non-communicable diseases, complications, and problems. The methodology of this survey is robust for a population-based study. We took comprehensive steps to ensure the validity and reliability of the findings. The findings indicate an urgent need for targeted public health interventions to address the escalating health issues. By focusing on prevention and early intervention strategies, we can mitigate the impact of NCDs on the healthcare system and improve overall population health.